Incidence and predictors of intracranial bleeding after coronary artery bypass graft surgery - Kim, Ju Hyeon; Lee, Pil Hyung; Kim, Ho Jin; Kim, Joon Bum; Park, Sojeong; Kyoung, Dae-Sung; Kang, Soo-Jin; Lee, Seung-Whan; Kim, Young-Hak; Lee, Cheol Whan; Chung, Cheol Hyun; Lee, Jae Won; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: There is a paucity of direct data on the incidence and predictors of intracranial bleeding (ICB) after coronary artery bypass graft surgery (CABG). Methods: The Korean National Health Insurance database was used to identify patients without prior ICB who underwent CABG. The outcomes of interest were the time-dependent incidence rates of ICB and the associated mortality. Results: Among 35,021 patients who underwent CABG between 2007 and 2018, 895 (2.6%) experienced an ICB during a median follow-up of 6.0 years. The 1-year cumulative incidence of ICB was 0.76%, with a relatively high incidence rate (9.93 cases per 1000 person-years) within the first 1–30 days. Subsequent incidence rates showed a sharp decline until 3 years, followed by a steady decrease up to 10 years. The 1-year mortality rate after ICB was 38.1%, with most deaths occurring within 30 days (23.6%). The predictors of ICB after CABG were age ≥75 years, hypertension, pre-existing dementia, history of stroke or transient ischemic attack, and end-stage renal disease. Conclusions: In an unselected nationwide population undergoing CABG, the incidence of ICB was non-negligible and showed a relatively high incidence rate during the early postoperative period. Post-CABG ICB was associated with a high risk of premature death. Further research is needed to stratify high-risk patients and personalize therapeutic decisions for preventing ICB after CABG.